Influência das épocas de colheita na qualidade de tomate cultivado em sistemas alternativos - Casa, Jamille; Evangelista, Regina Marta [UNESP] (Universidade Estadual de Londrina (UEL), 2009)
On tomato production in Brazil, around two/thirties is designated to consume "in nature". Thus, the skin aspect and its quality became an important factor on buying decision. Tomato presents high mass of water, and its quality depends on temperature and humidity variation. Water loss brings weight and fruit aspect loss, affecting the quality. This work aimed to verify the influence of harvest season on the fruit quality grown in alternative, organic and biodynamic systems. It was evaluated tomato quality characteristics, including mass loss, texture, pH, titratable acidity, soluble solids. The cycle stage of the tomato plant interferes on fruit quality. The third, fourth and fifth harvests were those which showed the highest values to quality parameters, with more fresh mass fruit. The sixth harvest showed fruits with high total soluble solids and sugar contents. on the evaluation of mass loss on the three harvest seasons, it was observed that on the first harvest there was a smaller loss. The period of harvest cycle interferes on the time of storage, and fruitd harvested on the first have more conservation time in relation to the other ones.
Harvest season influences on the quality of tomato grown in alternative systems
Keywords: Solanum lycopersicum; cyclo stage; crop system; fruit quality